The Decline of Investment in East Asia since the Asian Financial Crisis: An Overview and Empirical Examination - Dong-hyun Park; Kwanho Shin; Juthathip Jongwanich (Asian Development Bank (ADB), 2009)
A key legacy of the Asian financial crisis of 1997–1998 is a sustained drop-off in the investment rates of East Asian countries that were hardest hit by the crisis. We first review the stylized facts of investment in those countries, and then explore and evaluate the various possible explanations for the decline in investment. In our empirical analysis, which expands upon Park and Shin (2009) by updating the data to include 2005–2008, we investigate the extent to which the investment rates of Asian countries can be explained by the underlying fundamental determinants of investment such as gross domestic product (GDP) growth and demographic variables. We also empirically revisit the various hypotheses put forth to explain the investment drop-off, in particular competitive pressures from the People's Republic of China and heightened risk and uncertainty. Our analysis yields two main findings: (i) some evidence of overinvestment in the precrisis period but (ii) very little evidence of underinvestment in the postcrisis period. The results suggest that investment rates are currently more or less at appropriate levels despite their postcrisis decline. The salient policy implication is that quantitatively boosting investment may be less important for future growth than enhancing the investment climate.
hdl:11540/1846
Keywords: E22; 330; Investment; capital accumulation; growth slowdown; East Asia; Asian crisis; Finanzkrise; Auslandsinvestition; Volatilität; Wirkungsanalyse; China; Ostasien